IPO underpricing and outside blockholdings - Field, Laura Casares; Sheehan, Dennis P. (Journal of Corporate Finance, 2004)
Recent papers have proposed a link between underpricing of an initial public offering (IPO) and the resulting ownership structure of the firm. Brennan and Franks [J. Financ. Econ. 45 (1997) 391] hypothesize that IPO managers want to discourage new blockholdings to reduce the likelihood of being monitored. They show that underpricing encourages oversubscription, allowing discrimination against large blockholders. Conversely, Stoughton and Zechner [J. Financ. Econ. 49 (1998) 45] hypothesize that managers underprice to encourage investment by blockholders who provide monitoring services. We find that the link between underpricing and ownership structure is weak. Most firms have outside blocks in place at the IPO and retain them afterwards. In terms of acquiring new blockholders, there is no difference between firms that underprice and those that do not.